Gen Z’s Gender, Hedonic Shopping Motives and Impulse Buying - Rosmaniar, Asyidatur (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
Abstract The usage of cheap internet access via cell phones, along with the fact that Gen Z is growing up in the era of globalization, has resulted in a generation that is completely reliant on the internet. The goal of this study was to see how hedonic shopping motives and gender influenced Gen Z's impulse internet purchases. The participants in this study were Management Study Program students who made online purchases through Shopee. The participants in this study are management students between the ages of 18 and 26. Purposive sampling was utilized as the sample approach. Multiple Linear Regression with Dummy Variables was used to determine the effect of hedonic shopping motives and gender on impulse buying at Shopee. The t test and the test of the coefficient of determination are used to test hypotheses. Multiple Linear Regression results with dummy variables show that the results indicating that the hedonic shopping motives have a favorable and significant effect on impulse buying, whereas gender has no effect on impulse buying